2019
DOI: 10.1108/ijqrm-01-2018-0011
|View full text |Cite
|
Sign up to set email alerts
|

Understanding and evaluating teaching effectiveness in the UK higher education sector using experimental design

Abstract: Purpose The purpose of this paper is to demonstrate the power of experimental design as a technique to understand and evaluate the most important factors which influence teaching effectiveness for a postgraduate course in a higher education (HE) context. Design/methodology/approach The methodology involves the execution of a case study in the form of an experiment in a business school setting. The experiment was carried out with the assistance of over 100 postgraduate students from 26 countries. The data wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 34 publications
0
16
0
Order By: Relevance
“…In 66.7% of the case studies, the number of factors were less than or equal to five, as shown in Figure 8. The studies that included more than ten factors used either the (Antony et al, 2019;Bell et al, 2006) or the Taguchi method (Bleier et al, 2019;Shahin et al, 2012) to identify the most significant factors. Some experimenters utilised Plackett-Burman designs to separate out the vital few factors from the trivial many.…”
Section: Number Of Factors Levels and Quality Characteristicsmentioning
confidence: 99%
See 3 more Smart Citations
“…In 66.7% of the case studies, the number of factors were less than or equal to five, as shown in Figure 8. The studies that included more than ten factors used either the (Antony et al, 2019;Bell et al, 2006) or the Taguchi method (Bleier et al, 2019;Shahin et al, 2012) to identify the most significant factors. Some experimenters utilised Plackett-Burman designs to separate out the vital few factors from the trivial many.…”
Section: Number Of Factors Levels and Quality Characteristicsmentioning
confidence: 99%
“…Concerning the applications of DoE in the higher education sector, Antony et al (2019) and Ree et al (2014) reported the difficulty of measuring responses due to the subjectivity involved among the participants. Antony et al (2014) mentioned that the challenge was the small number of students that participated in the study and the fact that the experiment was confined to only one module.…”
Section: Challenges Identified In the Doe Applicationsmentioning
confidence: 99%
See 2 more Smart Citations
“…If not handled properly, it will have a serious impact on the country and society [7,8]. Therefore, the development of online teaching can ensure the progress of teaching, and at the same time, this novel teaching method can also make students happily absorb knowledge [9,10].…”
Section: Introductionmentioning
confidence: 99%